1995
DOI: 10.1002/aja.1002040107
|View full text |Cite
|
Sign up to set email alerts
|

Tissue‐nonspecific alkaline phosphatase participates in the establishment and growth of feather germs in embryonic chick skin cultures

Abstract: Alkaline phosphatase activity is present in the mesoderm of embryonic chick skin and becomes spatially restricted to the dermal condensation of the developing feather germs. Inhibitors to tissue-nonspecific (liver/bone/kidney), but not intestinal, alkaline phosphatase inhibit the establishment and growth of feather germs in cultured skins. A window of maximum sensitivity to the inhibitor was observed to be the first day of culture when early development and establishment of pattern takes place. The cDNA for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…In control combinations of chick skin epithelium and skin mesenchyme, mesenchymal AP activity was detected weakly in only 1 case of 20 in the feather germs that formed (Table 1), probably because feather germ AP activity is heat labile and therefore inactivated during embedding (32,34). Weak epithelial AP staining also was observed in five cases, including that in which the weak mesenchymal activity was observed (Table 1).…”
Section: Induction Of Distinct Epithelial Appendages In Heterotypic mentioning
confidence: 85%
See 1 more Smart Citation
“…In control combinations of chick skin epithelium and skin mesenchyme, mesenchymal AP activity was detected weakly in only 1 case of 20 in the feather germs that formed (Table 1), probably because feather germ AP activity is heat labile and therefore inactivated during embedding (32,34). Weak epithelial AP staining also was observed in five cases, including that in which the weak mesenchymal activity was observed (Table 1).…”
Section: Induction Of Distinct Epithelial Appendages In Heterotypic mentioning
confidence: 85%
“…The molecular markers we have used, Shh and AP, although consistent with a tooth fate, both are expressed in other developmental contexts, including developing feather germs (32,34). Although the structures that formed in the heterotypic recombinants do not resemble feather germs nor do they express the same heat-stable AP isoform, these markers are general to other epithelial-mesenchymal interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Four distinct genes encoding ALP have been identified in mammals, whereas two of these forms, IAP and TNAP, have been reported in birds (26). In DT40 cells, the TNAP mRNA alone was detected by RT-PCR and ALP activity in DT40 cells was completely inhibited by levamisole, a specific inhibitor of TNAP, which indicated that DT40 cells exclusively express TNAP of ALPs.…”
Section: Znt5 and Znt7 Are Essential For Alp Activitymentioning
confidence: 86%
“…These processes are most probably confined to the dermis because the activity measured in the epidermis was found to be less than 1% of the activity of the underlying dermis (Mier and van Rennes, 1982). In general, the cutaneous ALP seems to be of a tissue-non-specific type, present in the dermal condensations of developing feather germs, hair follicles, capillaries and sweat glands (Mier and van Rennes, 1982;Crawford et al, 1995;Saga and Morimoto, 1995). Furthermore, it is present in both a soluble and a membrane-bound form (Mier and van Rennes, 1982).…”
Section: M Peltonen and S Mänttärimentioning
confidence: 99%
“…Plasma ALP activity has been associated with boneforming activity by osteoblasts, and with other tissues that have high cellular turnover (Bell, 1971). Since the tissue-non-specific ALP is synthesized in the skin (Yamashita et al, 1987;Crawford et al, 1995;Hui and Tenenbaum, 1995), and may be involved in physiological and pathological mineralization in tissues other than bone or cartilage (Hui et al, 1997), we also measured its activity in the cutaneous interstitial fluid.…”
Section: +mentioning
confidence: 99%